Genetic Associations Between Specific Sleep-Related Phenotypes and Idiopathic Sudden Sensorineural Hearing Loss: A Mendelian Randomization Analysis - Li M; He J; Liang Y; Zou F; Gou C; Lv J; Zhang X; Li D; Yu Z (Nature and Science of Sleep)
Man Li,1,* Jinbo He,2,* Yiting Liang,3 Fan Zou,1 Changlong Gou,4 Jing Lv,2 Xicheng Zhang,5 Dan Li,6 Zizhong Yu1 1Department of Otolaryngology, Head and Neck Surgery, Taihe Hospital, Hubei University of Medicine, Shiyan, 442000, People’s Republic of China; 2Department of Anesthesiology, Taihe Hospital, Hubei University of Medicine, Shiyan, 442000, People’s Republic of China; 3First Clinical College, Hubei University of Medicine, Shiyan, 442000, People’s Republic of China; 4Department of Ultrasound Medicine, Taihe Hospital, Hubei University of Medicine, Shiyan, 442000, People’s Republic of China; 5Biomedical Engineering College, Hubei University of Medicine, Shiyan, 442000, People’s Republic of China; 6Clinical Molecular Diagnostic Center, Taihe Hospital, Hubei University of Medicine, Shiyan, 442000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zizhong Yu, Department of Otolaryngology, Head and Neck Surgery, Taihe Hospital, Hubei University of Medicine, No. 32 Renmin South Road, Maojian District, Shiyan, Hubei, 442000, People’s Republic of China, Tel +86-719-8801459, Email yurick0994@163.com Dan Li, Clinical Molecular Diagnostic Center, Taihe Hospital, Hubei University of Medicine, No. 32 Renmin South Road, Maojian District, Shiyan, Hubei, 442000, China, Tel +86-719-8801881, Email lidan198016@163.comPurpose: The relationship between idiopathic sleep-related phenotypes (SRPs) and sudden sensorineural hearing loss (ISSNHL) remains unclear. This study was designed to investigate the link between SRPs and ISSNHL from a genetic perspective through Mendelian randomization (MR) analysis.Methods: ISSNHL trials were downloaded from Finngen database. SRPs were from the UK Biobank and FinnGen database. The inverse variance weighted (IVW) method was utilized, followed by confirming the robustness and reliability using the MR Egger, weighted median, simple mode, and weighted mode. The heterogeneity was determined using MR Egger and IVW, and pleiotropy by MR Egger.Results: There were 39/27 single nucleotide polymorphisms (SNPs) related to insomnia, 68 SNPs related to sleep duration, 31 SNPs related to daytime dozing, 13 SNPs related to sleep disorders, and 20 SNPs related to sleep apnoea. The F statistics exceeded 10, suggesting minimal likelihood of weak instrument bias. There were no evidence indicating a potential causal effect of insomnia, sleep duration, sleep disorders, sleep apnoea, and on the risk of ISSHNL. However, narcolepsy was an inferred protective factor for ISSNHL. Lower risk of ISSNHL was found in relation to daytime dozing/sleeping (narcolepsy)-related SNPs.Conclusion: This phenomenon may provide a novel and meaningful therapeutic target for ISSNHL based on sleep medicine. However, this putative causal relationship requires further experimental validation.Keywords: ISSNHL, hearing loss, sleep-related phenotypes, Mendelian randomization